Foreign Body as Cause of Submandibular Swelling in an Infant. Issue 8 (August 2016) - Gonzalez de Alba, Cesar; Garcia, Elizabeth; Molina Berganza, Fernando; Fergie, Jaime
Abstract : Supplemental Digital Content is available in the text.